Turnover at the Top: The Digital Transformation and Dismissal of Chairman and CEO - Qi, Jipeng; Zhou, Yaxian; Lv, Wendai; Du, Qiyue; Liu, Ran; Liu, Caixing (Frontiers in Psychology, 2022)
Companies increasingly implement digital transformation strategies to promote efficiency. Nevertheless, there are few concerns about employees' acceptance of the changes, especially the executives' adaptability, which is an important part of digital transformation strategy implementation. By utilizing the “searching-matching” in keywords of the annual reports of public listed companies in China, we measured the degree of corporate digital transformation to analysis its influence on the turnover rate of Chairman and CEO. We found that digital transformation decreases the possibility of Chairman and CEO' turnover. Derived from the dynamic managerial capital theory, we demonstrated that executives’ social network and political connections both have a moderate effect on the relationship between digital transformation and the turnover rate of executives. These findings will contribute to digital transformation research by integrating with executives' dynamic managerial capital which is attained through social networks and political connection.